Dampak Struktur Kepemilikan, Financial Leverage, Board Director terhadap Nilai Perusahaan - Sri Dwi Ari Ambarwati; Rini Dwi Astuti (Jurnal Keuangan dan Perbankan, 2015)
This study tried to analyze the effect of ownership structure, financial leverage, size of board directors and sales Growth on the performance of companies with lower growth opportunities , whether there is a proxy growth opportunities with low PER. This research was conducted at the manufacturing company with the selection criteria for purposive sampling method 2010-2012 period, based on the criteria the obtained sample of 32companies with low growth opportunities. Thus obtained 96 obervasi for each group. The results showed that: 1). simultaneously the ownership structure, financial leverage, size of board directors and sales Growth affect the performance of companies with low growth opportunities. 2). Partially, it was found empirical evidence that financial leverage and variable size of board directors significantly affect the companys performance with lower growth opportunities. For institutional ownership structure revealed a significant effect on performance, but at a rate of 10% alpha tolerated.